Bibliometric Mapping of Technology Acceptance Model and Electronic Service Quality Research: The Position of Digital Public Services - Tiara Aidil Fitri; Iip Permana (YASIN, 2026)
Digital transformation has established the Technology Acceptance Model (TAM) and the Electronic Service Quality (E-S-QUAL) framework as prominent theoretical perspectives for explaining technology adoption and digital service performance; however, the position of digital public service within this research landscape remains empirically unclear. This study maps the relative position of digital public service within the intellectual structure of TAM and E-S-QUAL research. A bibliometric approach was applied to 1,000 documents published between 2016 and 2026 and retrieved from Google Scholar through Publish or Perish using the keywords “Technology Acceptance Model,” “Electronic Service Quality,” “Digital Public Service,” “Perceived Usefulness,” and “Perceived Ease of Use.” The data were analyzed using VOSviewer 1.6.21 through bibliometric network mapping, yielding 211 keyword items across eight clusters, 6,468 links, and a total link strength of 25,815. The findings demonstrate that digital public service occupies a peripheral position within the broader TAM and E-S-QUAL research landscape. Public-sector terms, including “public administration,” “e-government,” and “citizen,” were substantially less prominent than commercial constructs such as “usefulness” and “mobile banking” and education-related terms such as “higher education.” This thematic imbalance indicates that public administration has not yet become a central domain within technology acceptance research despite the rapid expansion of digital government initiatives. The study contributes a bibliometric overview of the underrepresentation of digital public service in TAM and E-S-QUAL scholarship and identifies opportunities to extend these frameworks toward digital governance, citizen-centered service design, and public trust.